Toward Commercialization of Efficient and Stable Perovskite Solar Modules. Issue 3 (10th October 2021) - Yang, Chenquan; Zhi, Rui; Rothmann, Mathias Uller; Huang, Fuzhi; Cheng, Yi-Bing; Li, Wei
Abstract : The commercialization of perovskite photovoltaic technology is dependent on the development of high‐efficiency, stable, and large‐area solar modules. Despite the rapid rise in efficiencies of laboratory‐scale perovskite solar cells (PSCs), there is still a big gap in the transition from small‐area devices to large‐area perovskite solar modules (PSMs). Herein, recent progresses on scaling‐up PSMs are reviewed: first, multifarious scalable preparation methods, solvent engineering, and corresponding morphology control strategies for large‐area homogeneous perovskite films are summarized. Various charge carrier transport materials, electrode materials, and their scaling methods for high‐efficiency and stable PSMs are then outlined and the device structure design of PSMs is discussed. Finally, the current strategies for optimizing the environmental stability of devices are highlighted, and packaging for reducing lead leakage during operation is discussed. Abstract : Herein, a systematic overview of commercialization of perovskite PV technology is provided, including module architecture, laser scribing, cost, and life cycle. The key strategies for fabrication, stability, and performance are also discussed. In addition, the current issues and future perspective are provided toward commercialization of perovskite solar modules in the near future.